COVID-19 inflammatory signature in a Mozambican cohort: unchanged red blood series and reduced levels of IL-6 and other proinflammatory cytokines - Vânia Maphossa; Onélia Guiliche; Teresa Babetine; Celso Castiano; Osvaldo Inlamea; Marino Marengue; Igor Capitine; Lúcia Chambal; Almiro Tivane; Jahit Sacarlal; Eugênia Terra-Granado; Raquel Matavele Chissumba (BMC Infectious Diseases)
Summary Background Alterations in haematological, biochemical parameters and cytokine levels, were reported in patients with COVID-19, however, there is an underrepresentation of the African population, which could provide evidence for understanding SARS-CoV-2 pathogenesis and useful tools for clinical management of cases. In this study, we aimed to determine the haematological, biochemical and cytokine profile in Mozambican individuals with SARS-CoV-2. Methods A cohort of 85 Mozambican individuals with RT-PCR SARS-CoV-2 results, was stratified into negative, asymptomatic, mild, moderate, and severe categories. Haematological, biochemical and cytokines measurement were performed on samples from the study participants. Principal component analysis (PCA) was performed to identify similar patterns among the study cases. Comparisons between groups were performed using the Kruskal-Wallis test. Receiver operating characteristic (ROC) and area under the curve (AUC) analysis were conducted to evaluate the ability of these parameters to distinguish severe from non-severe cases of SARS-CoV-2 infection. Results SARS-CoV-2 infection was associated with a significant (p < 0.05) decrease in peripheral blood absolute counts of total lymphocytes and eosinophils, below the reference values along with no abnormal change (p > 0.05) in red blood cell count, haemoglobin, platelets and other red series parameters. At the serum level, SARS-CoV-2 infection was associated with an increase in serum levels of C-reactive protein (C-RP) and glucose above the reference values and to a significant reduction a significant (p < 0.05) reduction in levels of interferon-gamma (INF-γ), Tumour Necrosis Factor alfa (TNF-α) and the interleukin 1 beta (IL-1β) and IL-6 in severe cases, when compared to negative cases. Haematological, biochemical and cytokine profiles segregate severe from non-severe cases of COVID-19 with an excellent performance of C-RP (AUC = 0.95; p < 0.001) and good performance of lymphocytes (AUC = 0.88; p < 0.001) and IL-15 (AUC = 0.86; p < 0.001). Conclusion The lack of variation in red and platelet series, coupled with a decrease in the levels of classical pro-inflammatory in severe cases, deviates from what has been reported in other contexts suggesting, that there may be peculiarities in COVID-19 manifestation within the context of this study population. Furthermore, these results identify parameters with potential for clinical management of COVID-19 and therefore good resource allocation, particularly for severe cases.